Gambaran Tingkat Pengetahuan Orang Tua Tentang Penanganan ISPA Pada Balita di Wilayah Kerja Puskesmas Palasari Subang - Lintang Bening Septivine; Ade Nuraeni; Nuridha Fauziyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Acute respiratory tract infection (ARI) is still one of the important public health problems to pay attention to, because it is an acute disease that can cause death of toddlers in various developing countries including Indonesia. This study aims to determine the level of parental knowledge about handling ARI in toddlers in the Palasari Subang Health Center work area. This research method uses quantitative descriptive with descriptive design. The sampling method in this study used purposive sampling with certain considerations of 55 people. The research instrument used a questionnaire for handling ARI. The results of this study are that the majority of respondents are 26-35 years old, namely 28 people (50.9%), most respondents are female with 47 people (85.5%), with most respondents working as housewives, namely 41 people (74.5%) and the last education is high school graduates, namely 28 people (50.9%). Where the results of the level of knowledge of respondents at the Palasari Subang Health Center, most respondents have moderate knowledge, namely 39 people (69.1%). It can be concluded that the level of knowledge of respondents regarding the handling of ISPA is mostly in the moderate category, the age of respondents is mostly 26-35 years old, the majority of respondents' jobs are as housewives and the majority of respondents' education is high school level. Parents' knowledge in the good category is expected to be able to increase their knowledge about the transmission of ISPA in toddlers by seeking information about ISPA in toddlers from cadres, health workers at health centers or other information media.